2022
DOI: 10.1002/cpt.2600
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Pharmacokinetic Modelling to Investigate Baricitinib and Tofacitinib Dosing Recommendations for COVID‐19 in Geriatrics

Abstract: Janus kinase (JAK) inhibitors baricitinib and tofacitinib are recommended by the US National Institutes of Health as immunomodulatory drugs for coronavirus disease 2019 (COVID‐19) treatment. In addition, baricitinib has recently received Emergency Use Authorization from the US Food and Drug Administration, although the instruction provided dosing information only for adults. Geriatrics with organ dysfunction are one of the most vulnerable cohorts when combating the pandemic. The aim of the present work was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“… 15 Our quantitative and mechanistical simulations verified the potent inhibition by both dosage regimens of ritonavir against enzymes and transporters associated with elimination of rivaroxaban, especially the comparable inhibition potency against CYP3A4 ( Figure S2 A,B ). Corroborating our previous studies, 19 , 20 prospective simulations revealed that geriatric patients with moderate renal dysfunction were more susceptible to the DDDIs between rivaroxaban and ritonavir, who could potentially benefit from a further dose adjustment to 10 mg daily rivaroxaban while receiving nirmatrelvir/ritonavir treatment. Considering the enzyme half‐lives of 20–30 hours for CYP3A4 and CYP2J2 and simulated recoveries of CYP3A4 (liver), CYP3A4 (gut), and CYP2J2 activities post‐MBI by ritonavir were 62.4%, 82.1%, and 77.6%, respectively, the reduced dose of rivaroxaban could be maintained for 3 days post‐nirmatrelvir/ritonavir treatment, which was in accordance with recommendations by Marzolini et al .…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“… 15 Our quantitative and mechanistical simulations verified the potent inhibition by both dosage regimens of ritonavir against enzymes and transporters associated with elimination of rivaroxaban, especially the comparable inhibition potency against CYP3A4 ( Figure S2 A,B ). Corroborating our previous studies, 19 , 20 prospective simulations revealed that geriatric patients with moderate renal dysfunction were more susceptible to the DDDIs between rivaroxaban and ritonavir, who could potentially benefit from a further dose adjustment to 10 mg daily rivaroxaban while receiving nirmatrelvir/ritonavir treatment. Considering the enzyme half‐lives of 20–30 hours for CYP3A4 and CYP2J2 and simulated recoveries of CYP3A4 (liver), CYP3A4 (gut), and CYP2J2 activities post‐MBI by ritonavir were 62.4%, 82.1%, and 77.6%, respectively, the reduced dose of rivaroxaban could be maintained for 3 days post‐nirmatrelvir/ritonavir treatment, which was in accordance with recommendations by Marzolini et al .…”
Section: Discussionsupporting
confidence: 64%
“… 5 Healthy population (Healthy Volunteers), general White population (NEurCaucasian) and geriatric population (Geriatric NEC) provided in Simcyp were adopted as population models. The moderate renal impairment (creatinine clearance (CrCL) 30 to 49 mL/min) population model modified previously 19 , 20 were utilized for simulations. Each simulation was designed as a total size of 100 subjects (10 trials with 10 subjects for each).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The latter is the topic of a series of articles in the current issue of CPT, which covers therapeutic treatment and evaluation in patient groups across the full age range, from preterm infants to geriatrics (Figure 1). [2][3][4][5][6] On one end of the patient age spectrum, Engbers et al 2 examine the exposure-response relationship of ibuprofen on closure of the patent ductus arteriosus in preterm infants. Their model-based analysis provides new insights into the role of ibuprofen exposure, covariates, and timing of treatment on clinical outcomes.…”
Section: Diversity In Clinical Pharmacology Coming Of Agementioning
confidence: 99%